(3GdfbGjI aj Yde GdOQGjIs - (3YHO GdQMef Hf CHj HcQ Hf eMeO GdNVjQj GdSjhWj, CHh GdaVd , LdGd GdOjf , J (B911 (3g`s
(3ChdgG (B:s
(3GdMeO ddg hGdTcQ dg gPg fbGjI ef YOg Ydhe jMJGL GdWGdH EdjgG CUhd GdOjf Yde jHMK ajg YeG jLH EYJbGOg GdYGde MGOK , hUGfYI Gddg GdhGMO bOje dGEHJOGA dhLhOg , hdG GfJgi s
(3BNQgG (B:s
(3NGJeI (B: (3GdYde CS GdYed , hKeQJg , hbdjdg eYg NjQ ef cKjQg eY Lgd , aef Ke cGf CaVd ef UdGI GdfGadI hjMQe Yde GdadGSaI cGdefWb , hGdUdGI CaVd ef GdWhGa hef ZjQg Cg` s
(3HgG fXGe GdJYbjHIs
(3cJHJ HYV GdYHGQGJ HGdMeQIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B301 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B535s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1970s
(3JHUQGJ GdCUd (B:s
Keywords: (3CUhd Gdabgs